Colon and gut microbiota greatly affect the absorption and utilization of astaxanthin derived from Haematococcus pluvialis. (June 2022) - Li, Chunjun; Gao, Yuan; Huan, Yuchen; Ren, Pengfei; Zhi, Jinjin; Wu, Axue; Xu, Jie; Wei, Zihao; Xue, Changhu; Tang, Qingjuan
Graphical abstract: Highlights: The colon has an ability to absorb astaxanthin derived from Haematococcus pluvialis. Gut microbiota greatly influences the absorption of astaxanthin. The structure of astaxanthin is altered by gut microbiota. Lactobacillus may play an important role in the absorption of astaxanthin. Abstract: Astaxanthin has been widely favored as a health food supplement by individuals but its absorption in the body seems not to be satisfactory. In addition, the peak time of astaxanthin derived from Haematococcus pluvialis in the plasma was much longer than other carotenoids found in our previous research. Thus, it is necessary to explore the process that affects the absorption of astaxanthin in order to potentially find a novel approach to improve the absorption in the future. In this study, we confirmed that the colon has an ability to absorb astaxanthin and conducted acute feeding experiments with the treatment of antibiotics in C57BL/6J mice and chronic feeding experiments in germ-free (GF) mice to detect the relationship between the gut microbiota and the absorption of astaxanthin. Our study showed that the decrease of gut microbiota led to a less oral absorbability, which might be related to the decreased expression of SR-BI in the small intestine and the reduction of free form and Z -astaxanthin converted by the gut microbiota found in the vitro culture. The experiments of anaerobic culture also implied that Lactobacillus might play an important role in the absorption of astaxanthin.